2021
DOI: 10.2196/23842
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Pregnant and Breastfeeding Women on Participating in Longitudinal Mother-Baby Studies Involving Electronic Health Records: Qualitative Study

Abstract: Background Electronic health records (EHRs) hold great potential for longitudinal mother-baby studies, ranging from assessing study feasibility to facilitating patient recruitment to streamlining study visits and data collection. Existing studies on the perspectives of pregnant and breastfeeding women on EHR use have been limited to the use of EHRs to engage in health care rather than to participate in research. Objective The aim of this study is to exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…These trust issues relate to ndings of Simon et al who reported on the trust barriers of minorities in the US towards using electronic informed consents and privacy and con dentiality concerns of rural participants [19]. Concerns about privacy and con dentiality were also reported by Hentschel and colleagues to be one of the dominant factors in pregnant women's willingness to share electronic health records of themselves and their infant [21]. In order to create more trust among parents in the digital informed consent procedure, it might be helpful to invest in personal face to face contact.…”
Section: Challenges When Using An Identi Cation Systemmentioning
confidence: 87%
“…These trust issues relate to ndings of Simon et al who reported on the trust barriers of minorities in the US towards using electronic informed consents and privacy and con dentiality concerns of rural participants [19]. Concerns about privacy and con dentiality were also reported by Hentschel and colleagues to be one of the dominant factors in pregnant women's willingness to share electronic health records of themselves and their infant [21]. In order to create more trust among parents in the digital informed consent procedure, it might be helpful to invest in personal face to face contact.…”
Section: Challenges When Using An Identi Cation Systemmentioning
confidence: 87%
“…As such, our respondent pool was 56.8% white in this study compared to 69.0% white in a prior study that recruited solely from face-to-face encounters in an academic hospital setting. 14 Social mediabased recruitment may be a particularly beneficial strategy to diversify the clinical research recruitment arsenal as well as diversify the participant pool to be more representative of the socioeconomic and racial/ethnic make-up of the population.…”
Section: Social Mediamentioning
confidence: 99%
“…Barriers to research participation at individual-level included concerns about privacy and confidentiality as well as time commitment. 11,12,14 Community-level barriers included inadequate clinical support 15 , study risks 16 , and the uncertainty around characterizing the research or intervention 12 . However, these observations were all conducted before the COVID-19 pandemic and there is a critical need to understand the perspectives of these populations during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Mommy's Milk biorepository has collected over 80,000 milk aliquots, including many longitudinal samples, paired infant biospecimens, and clinical data 78 . Even so, clinical data gathered from electronic health records may not always be complete – for example, the records may report antibiotics prescribed directly to the infant but not those prescribed to the lactating parent 79,80 . Medical records also do not consistently include the use of over‐the‐counter medications and supplements, such as probiotics, which could affect microbiome development.…”
Section: Untargeted Metabolomics In Drug Metabolismmentioning
confidence: 99%